Disturbed habitats locally reduce the signal of deep evolutionary history in functional traits of plants. Issue 4 (27th September 2021) - Prinzing, Andreas; Pavoine, Sandrine; Jactel, Hervé; Hortal, Joaquin; Hennekens, Stephan M.; Ozinga, Wim A.; Bartish, Igor V.; Helmus, Matthew R.; Kühn, Ingolf; Moen, Daniel S.; Weiher, Evan; Brändle, Martin; et al.
Summary: The functioning of present ecosystems reflects deep evolutionary history of locally cooccurring species if their functional traits show high phylogenetic signal (PS). However, we do not understand what drives local PS. We hypothesize that local PS is high in undisturbed and stressful habitats, either due to ongoing local assembly of species that maintained ancestral traits, or to past evolutionary maintenance of ancestral traits within habitat species‐pools, or to both. We quantified PS and diversity of 10 traits within 6704 local plant communities across 38 Dutch habitat types differing in disturbance or stress. Mean local PS varied 50‐fold among habitat types, often independently of phylogenetic or trait diversity. Mean local PS decreased with disturbance but showed no consistent relationship to stress. Mean local PS exceeded species‐pool PS, reflecting nonrandom subsampling from the pool. Disturbance or stress related more strongly to mean local than to species‐pool PS. Disturbed habitats harbour species with evolutionary divergent trait values, probably driven by ongoing, local assembly of species: environmental fluctuations might maintain different trait values within lineages through an evolutionary storage effect. If functional traits do not reflect phylogeny, ecosystem functioning might not be contingent on the presence of particular lineages, and lineages might establish evolutionarily novel interactions.